The Role of the Teacher in the Motivation of the Student - Kumar, Gaurav; Sharma, Aarshiya (Journal of Advanced Research in English & Education; Vol 3 No 4 (2018): Journal of Advanced Research in English & Education, 2018)
The foreign language teacher has the role of transmitting to students not only linguistic knowledge but is also endowed with the responsibility of instilling the values that an acquisition process requires to be fruitful. "The teacher influences, consciously or unconsciously, that what the students want to know, knows how to think and develop their knowledge in a way that helps positively and not negatively in learning, memory and use of information” (Alonso Tapia, 1991). The teacher assesses the needs of the students and makes the learning process relevant, creates a relaxed environment in the classroom and fosters feelings of self-confidence and self-esteem, instills feelings of autonomy and responsibility, provides useful feedback and makes the student see the value that academic activities can have on their personal development outside the classroom. This research will discuss instructional motivational strategies that are based on the prescriptive motivational models of Dornyei (1998) and Brophy (1987) but are adapted to better accommodate the needs of the Indian context. How to cite this article: Gaurav Kumar, Aarshiya Sharma. The Role of the Teacher in the Motivation of the Student. J Adv Res Eng & Edu 2018; 3(4): 31-36. DOI: https://doi.org/10.24321/2456.4370.201805